2019
DOI: 10.1126/sciadv.aau7555
|View full text |Cite
|
Sign up to set email alerts
|

Rapid isotopic exchange in nanoparticles

Abstract: Rapid isotopic exchange reveals the solution-state dynamics existing in nanoparticles, very similar to that in H2O and D2O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…The metastable species transform their geometrical structures into thermodynamically stable ones in solution through inter‐cluster (and intra‐cluster) metal exchange (metal exchange of type 3; Figure A and Figure 15B (a); 2) when [Au 38− x Ag x (SC 4 H 9 ) 24 ] 0 is synthesized by simultaneously reducing Au and Ag salts (co‐reduction [ 145 ] ), thermodynamically stable NCs can be mainly synthesized, and inter‐cluster metal exchange is relatively suppressed for those NCs (Figure 15B (b)). The observed phenomenon occurred under this experimental condition, and even if the same [Au 38 −x Ag x (SC 4 H 9 ) 24 ] 0 was used, the dynamic behavior might differ depending on the temperature [ 261 ] or concentration used. The reaction rate also appears to be different when the functional group structure of the ligand or/and the number of Ag substitutions differ.…”
Section: Recent Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The metastable species transform their geometrical structures into thermodynamically stable ones in solution through inter‐cluster (and intra‐cluster) metal exchange (metal exchange of type 3; Figure A and Figure 15B (a); 2) when [Au 38− x Ag x (SC 4 H 9 ) 24 ] 0 is synthesized by simultaneously reducing Au and Ag salts (co‐reduction [ 145 ] ), thermodynamically stable NCs can be mainly synthesized, and inter‐cluster metal exchange is relatively suppressed for those NCs (Figure 15B (b)). The observed phenomenon occurred under this experimental condition, and even if the same [Au 38 −x Ag x (SC 4 H 9 ) 24 ] 0 was used, the dynamic behavior might differ depending on the temperature [ 261 ] or concentration used. The reaction rate also appears to be different when the functional group structure of the ligand or/and the number of Ag substitutions differ.…”
Section: Recent Developmentmentioning
confidence: 99%
“…Currently, the number of methods for observing the geometrical structure of the reaction intermediates generated in solution is limited. However, if the number of such structural analysis methods [ 249,261 ] increases in the future, it should become possible to obtain a deeper understanding of the reaction processes. In addition, it is expected that methods to stop the reaction on the way and thereby to obtain alloy NCs with heteroatoms of different substitution sites will be established.…”
Section: Recent Developmentmentioning
confidence: 99%
“…Isotopic exchange reactions have been widely used to understand dynamics in the structures of proteins and polymers. Similarly, isotopic exchange in NCs also resolved their structural dynamics. , Two Ag 25 (DMBT) 18 – NCs, prepared with isotopically pure 107 Ag and 109 Ag, respectively, reacted to produce isotopically mixed Ag 25 (DMBT) 18 – . The isotopic exchange was similar to the exchanges observed in H 2 O and D 2 O, which revealed that NCs indeed behave as simple molecules.…”
Section: Introductionmentioning
confidence: 78%
“…Isotopically pure 107 Ag 25 (DMBT) 18 – and 109 Ag 25 (DMBT) 18 – NCs were synthesized using isotopically pure 107 AgNO 3 and 109 AgNO 3 salts and following the previously established synthetic protocols. , Details of synthesis are mentioned in the Supporting Information, and ESI MS of the NCs is presented in Figure S1.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Salassa et al used MALDI MS and NMR spectroscopy to show that monolayers of clusters are dynamic in nature, and inter-cluster ligand exchanges can occur during collision between the NCs 111 . Using isotopically pure silver clusters made of 107 Ag and 109 Ag, Chakraborty et al studied rapid isotopic exchange in silver clusters by HR ESI MS and found that the solution-state exchange dynamics of the clusters is similar to that occurring in water (H 2 O + D 2 O = 2HDO) 112 .…”
Section: Reactions Between Nanoparticlesmentioning
confidence: 99%